The rhythm window - Niebuhr, Oliver (Revista Leitura, 2014)
The paper presents a combined production and perception study on speech rhythm in German. The perception part shows that identifying complex rhythm patterns is only possible for speaking rates of 4-8 syll/sec. Even acoustically monotonous stimuli within this range trigger “subjective rhythms”. In contrast, rhythm perception is flattened for speaking rates outside this range, irrespective of acoustic cues to rhythm. The production part accords with this finding. Speaking rates in everyday conversation vary between 4-8 syll/sec, and only fall below this range when speakers flatten their rhythm for emphatic purposes. Together, the production and perception evidence revealed a “rhythm window”, which is targeted or avoided by speakers. DOI: 10.28998/2317-9945.2013v2n52p67-93